2009
DOI: 10.1111/j.1365-2362.2008.02077.x
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits fatty acid and triacylglycerol synthesis in rat hepatocytes

Abstract: Results here reported show that in isolated hepatocytes from normal rats a resveratrol-induced short-term inhibition of fatty acid and triacylglycerol synthesis occurs. This finding may represent a potential mechanism contributing to the reported hypolipidemic effect of resveratrol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 40 publications
0
33
1
Order By: Relevance
“…Presumably, its inhibitory role in the late phase of adipogenesis is likely to be due to modulation of either lipogenesis or lipolysis. Although little is known about the role of piceatannol in lipid metabolism, resveratrol has been shown to inhibit total fatty acid and triglyceride synthesis in adipocytes (51,52). Current evidence also suggests a role for resveratrol in stimulating lipolysis and fatty acid oxidation in adipocytes (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, its inhibitory role in the late phase of adipogenesis is likely to be due to modulation of either lipogenesis or lipolysis. Although little is known about the role of piceatannol in lipid metabolism, resveratrol has been shown to inhibit total fatty acid and triglyceride synthesis in adipocytes (51,52). Current evidence also suggests a role for resveratrol in stimulating lipolysis and fatty acid oxidation in adipocytes (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…The observed effects were accompanied by the decreased 3-hydroxy-3-methyl-glutaryl-CoA (HMG-CoA) reductase activity and reduced expression of its gene. In isolated hepatocytes, resveratrol decreased de novo synthesis of some fatty acids, reduced incorporation of acetate into triglycerides and decreased the activity of acetyl-CoA carboxylase; however, cholesterol synthesis and 3HMG-CoA reductase activity remained unchanged [12]. The studies performed by Barger et al [13] European Journal of Clinical Investigation Vol 39 899 DOI: 10.1111/j.1365-2362.2009.02188.x ORIGINAL ARTICLE revealed that even low doses of resveratrol provided in the diet can exert health protecting effects -the compound mimicked a calorie restriction inhibiting expression of genes engaged in cardiac and skeletal muscle ageing and increased insulin-stimulated glucose uptake.…”
Section: Introductionmentioning
confidence: 93%
“…Others compounds of similar activity include natural polyphenol (resveratrol) (Gnoni and Paglialonga, 2009) or macrocyclic polyketide (soraphen), which interacts with biotin carboxylase domain of ACCase and interferes with ACCase phosphorylation (Cho et al, 2010;Jump et al, 2011). Progress in the improvement of the properties of inhibitors depends on the assays for screening, validation and characterization of those compounds.…”
Section: Human Accase As Target In Diseases Treatmentmentioning
confidence: 99%